2021
DOI: 10.1371/journal.pone.0252397
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of STAT3 pathways in pancreatic adenocarcinoma: A systematic review of clinical and preclinical literature

Abstract: Background/Objectives Pancreatic ductal adenocarcinoma is a highly lethal disease with increasing incidence. Due to high resistance, chemo/radiotherapy has limited success in pancreatic cancer and only marginally prolongs patient survival. Therefore, novel biomarkers and therapeutic targets are needed. In the present review, we performed a comprehensive summary of therapeutic approaches targeting the GP130/JAK/STAT3 pathway. Methods We systematically reviewed the PubMed and Embase databases for preclinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Whereas targeting STAT3 remains a clinically promising target for solid tumors including PDAC, only a few clinical trials have shown favorable outcomes ( Peisl et al, 2021 ). However, many of these clinical studies do not examine the influence of the various STAT3 inhibitors on the stroma or immune cells ( Peisl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas targeting STAT3 remains a clinically promising target for solid tumors including PDAC, only a few clinical trials have shown favorable outcomes ( Peisl et al, 2021 ). However, many of these clinical studies do not examine the influence of the various STAT3 inhibitors on the stroma or immune cells ( Peisl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas targeting STAT3 remains a clinically promising target for solid tumors including PDAC, only a few clinical trials have shown favorable outcomes ( Peisl et al, 2021 ). However, many of these clinical studies do not examine the influence of the various STAT3 inhibitors on the stroma or immune cells ( Peisl et al, 2021 ). Despite many advances in the field of cancer immunotherapy, PDAC remains resistant to approved immunotherapeutic strategies, such as checkpoint inhibition therapy ( Royal et al, 2010 ; Brahmer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is constitutively activated in pancreatic cancer via phosphorylation of Tyr705, as found in human tumor specimens as well as in various pancreatic cancer cell lines [49,50]. An increasing number of studies have shown that STAT3 activation plays a pivotal role in the progression, metastasis, and drug resistance of pancreatic cancer [51,52].…”
Section: Discussionmentioning
confidence: 97%
“…Some STAT3 inhibitors have not shown a clear advantage in patients with pancreatic cancer [ 123 , 124 , 134 ]. Research on STAT3 inhibitors should focus on the following points: First, although STAT3 inhibitors have achieved good results in the experimental phase currently, they are limited by the limitations of monogenic drugs and further studies could be conducted to explore their use in combination with other classical chemotherapeutic drugs to improve the single- therapy of limitations and drug resistance to monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse events with AZD1480 occurred mainly neurologically, including dizziness, anxiety, ataxia, memory loss, hallucinations, and behavioral changes, and the cause of such adverse events is not known, leading to further clinical trials of the drug. In addition, JAK inhibitors such as momelotinib and ruxolitinib have also shown some adverse effects [ 123 ]. In patients with pancreatic cancer, 88% of patients reported grade 3 or 4 adverse events after using momelotinib [ 124 ].…”
Section: Stat3 Inhibitors and Cancermentioning
confidence: 99%